Cardiac MRI left ventricular global function index and quantitative late gadolinium enhancement in unrecognized myocardial infarction. Issue 92 (July 2017) - Krumm, Patrick; Zitzelsberger, Tanja; Weinmann, Melanie; Mangold, Stefanie; Rath, Dominik; Nikolaou, Konstantin; Gawaz, Meinrad; Kramer, Ulrich; Klumpp, Bernhard Daniel
Abstract: Purpose: To compare left ventricular global function index (LVGFI) and quantitative late gadolinium enhancement (LGE) in patients with unrecognized myocardial infarction (UMI), recognized myocardial infarction (RMI) and without myocardial infarction (MI). Material and methods: Under waiver of the Institutional Review Board 235 patients (age 63.5 ± 10.5 years, 57 female) were retrospectively evaluated. All patients had undergone cardiac MRI at 1.5T for symptoms of CAD. 67 patients (29%) had suffered a known RMI before. Functional imaging and full-intensity late gadolinium enhancement (LGE) imaging were evaluated for LVGFI and quantitative LGE mass. Results: Of 168 patients without history of RMI, 48 patients (29%) had UMI, 120 patients had no MI. LVGFI was lower in RMI patients (34 ± 8% [range 16;52]), and UMI patients (35 ± 8% [range 10;51]), compared to patients with no MI (38 ± 7% [range 16;55]) respectively and similar between RMI and UMI patients. RMI patients had full-intensity LGE in 11 ± 6% of left ventricular myocardial mass (LVMM). UMI patients had LGE in 9 ± 5% of LVMM. RMI patients had significantly more LGE than UMI patients (p = 0.0096). Conclusion: LGE quantification is effective to assess infarction scar size in RMI and UMI patients. LVGFI provides information on cardiac function and morphology but does not allow for a reliable differentiation between patients with and without history of MI, due small differences and wide overlap of LVGFI values for all three patient groups. This may be a reason why LVGFI is not applied in clinical routine.